2012
DOI: 10.4161/auto.8.2.18554
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine sensitizes breast cancer cells to chemotherapy independent of autophagy

Abstract: Chloroquine (CQ) is a 4-aminoquinoline drug used for the treatment of diverse diseases. It inhibits lysosomal acidification and therefore prevents autophagy by blocking autophagosome fusion and degradation. In cancer treatment, CQ is often used in combination with chemotherapeutic drugs and radiation because it has been shown to enhance the efficacy of tumor cell killing. Since CQ and its derivatives are the only inhibitors of autophagy that are available for use in the clinic, multiple ongoing clinical trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
262
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 344 publications
(277 citation statements)
references
References 45 publications
11
262
1
3
Order By: Relevance
“…More specifically, we have observed induction by radiation of a form of autophagy whose inhibition neither sensitizes nor protects the tumor cell from radiation. Dr. Thorburn's laboratory has also observed this nonprotective form of autophagy in response to cisplatin, 8 whereas we also have preliminary evidence for nonprotective autophagy in response to doxorubicin. 9 In this context, Lee et al recently reported that knockdown of SLC16A7/ MCT2 [solute carrier family 16, member 7 (monocarboxylic acid transporter 2)] in two primary forms of autophagy have been identified in the field of cancer therapy based on their apparent functions in the tumor cell; these are the cytoprotective form that could, in theory, be inhibited for the purpose of sensitization to radiation and chemotherapeutic drugs and the "cytotoxic" form that either mediates or contributes to the actions of these treatment modalities.…”
mentioning
confidence: 85%
“…More specifically, we have observed induction by radiation of a form of autophagy whose inhibition neither sensitizes nor protects the tumor cell from radiation. Dr. Thorburn's laboratory has also observed this nonprotective form of autophagy in response to cisplatin, 8 whereas we also have preliminary evidence for nonprotective autophagy in response to doxorubicin. 9 In this context, Lee et al recently reported that knockdown of SLC16A7/ MCT2 [solute carrier family 16, member 7 (monocarboxylic acid transporter 2)] in two primary forms of autophagy have been identified in the field of cancer therapy based on their apparent functions in the tumor cell; these are the cytoprotective form that could, in theory, be inhibited for the purpose of sensitization to radiation and chemotherapeutic drugs and the "cytotoxic" form that either mediates or contributes to the actions of these treatment modalities.…”
mentioning
confidence: 85%
“…Recent data indicate that only tumors that utilize excessive levels of autophagy, even in nutrientrich con ditions and in the absence of stressful stimuli, respond to autophagy inhibitors in vivo [117] . This suggests that only a fraction of cancer patients may benefit from the administration of autophagy inhibitors.…”
Section: Autophagy Drugs In Crcmentioning
confidence: 99%
“…Chloroquine diphosphate (CQ), an anti-malarial drug, shows potential anti-cancer effects, such as the inhibition of cell growth in human lung cancer A549 cells, human breast cancer cells, and glioma cells [8][9][10] . In addition, CQ therapy enhances the inhibitory effects of other chemotherapeutic agents on tumors.…”
Section: Introductionmentioning
confidence: 99%